Hong Kong Poison Information Centre: Annual Report 2012. Issue 6 (November 2013) - Chan, YC; Tse, ML; Lau, FL
Objective: To report and analyze the poisoning data of Hong Kong Poison Information Centre (HKPIC) in 2012. Methods: In 2012, all poisoning cases received by HKPIC were retrieved from its database: Poison Information and Clinical Management System (PICMS) for analysis. Results: A total of 4, 814 poisoned cases were analyzed. There were 1, 771 male patients (42.3%), 2, 399 female patients (57.3%) and 14 sex unspecified patients (0.3%). Middle aged group (30-39 years) contributed about one-fifth (20.1%) of the poisoning cases while more than two-third (67.7%) of them were between 20 and 59 years old. Common causes for poisoning were suspected self-harm/suicidal attempt (45%), abusive substances use (13.9%) and unintentional exposure (13.0%). Five commonest types of poison exposed were paracetamol, benzodiazepine, zopiclone, bites and envenomation and household products. Majority of the patients were managed with supportive measures, and 15.7% and 11.9% of them were treated by decontamination and antidotes respectively. Most cases had uneventful recovery; 0.6% of the poison exposure resulted in death and 4.7% of the exposure had major outcomes. Conclusions: This seventh annual report provides updated epidemiological information on poisoning pattern in Hong Kong and highlights important changes in comparing with our previous reports. (Hong Kong j.emerg.med. 2013;20:371-381)